Four new species and three taxonomic adjustments in Lachenalia (Asparagaceae: Scilloideae) from southern and western South Africa - Duncan, Graham D. (Phytotaxa, 2023)
A novel phylogenetic hypothesis for Lachenalia (Asparagaceae; Scilloideae; Hyacintheae) based on multilocus DNA sequence data has revealed the existence of four morphologically, ecologically and/or geographically distinct species, and supports the elevation of three existing subspecies to the species level. The new species and combinations are presented here. The new species are Lachenalia komsbergensis from the Komsberg in the southern Great Karoo (Northern Cape), Lachenalia inflata from the Hantam-Roggeveld escarpment in the western Great Karoo (Northern Cape), Lachenalia granitica from the Cape West Coast (Western Cape) and Lachenalia filamentosa from the Cape West Coast, Breede River Valley and Overberg (Western Cape). The taxa elevated from subspecies to species level are Lachenalia rogersii (previously L. mediana subsp. rogersii) from the Breede River Valley (Western Cape), Lachenalia glaucina (previously L. orchioides subsp. glaucina) from the southern Cape Peninsula (Western Cape) and Lachenalia parviflora (previously L. orchioides subsp. parviflora) from the northeastern Cape Peninsula (Western Cape).